2009
DOI: 10.1128/jb.00256-09
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequence of the Anaerobic, Thermophilic, and Cellulolytic Bacterium “ Anaerocellum thermophilum ” DSM 6725

Abstract: "Anaerocellum thermophilum" DSM 6725 is a strictly anaerobic bacterium that grows optimally at 75°C. It uses a variety of polysaccharides, including crystalline cellulose and untreated plant biomass, and has potential utility in biomass conversion. Here we report its complete genome sequence of 2.97 Mb, which is contained within one chromosome and two plasmids (of 8.3 and 3.6 kb). The genome encodes a broad set of cellulolytic enzymes, transporters, and pathways for sugar utilization and compared to those of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
82
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(83 citation statements)
references
References 10 publications
0
82
0
Order By: Relevance
“…Their genomes are also AϩT rich, ranging from 35 to 36% GϩC. Similarly to C. bescii (4,12), C. kristjanssonii also possesses an extrachromosomal element, the 15.9-kb plasmid pCALKR01. There are no similarities, however, between pATHE01/ pATHE02 and pCALKR01, suggesting that there are no ubiquitous Caldicellulosiruptor plasmids.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Their genomes are also AϩT rich, ranging from 35 to 36% GϩC. Similarly to C. bescii (4,12), C. kristjanssonii also possesses an extrachromosomal element, the 15.9-kb plasmid pCALKR01. There are no similarities, however, between pATHE01/ pATHE02 and pCALKR01, suggesting that there are no ubiquitous Caldicellulosiruptor plasmids.…”
mentioning
confidence: 99%
“…While 16S rRNA phylogeny indicates a very close relationship within the eight species studied thus far (94.8% to 99.4% identity), microbiological analysis indicated that the genus is more physiologically divergent than previously thought (2). Three complete genome sequences are currently available for this genus, those of C. saccharolyticus (19), C. bescii (12), and C. obsidiansis (5), all of which are capable of crystalline cellulose hydrolysis. To further probe the plant biomass-degrading capacity among Caldicellulosiruptor species, genome sequences of five additional members of this genus, including some hemicellulolytic but less cellulolytic members, were completed: those of C. hydrothermalis, C. kristjanssonii, C. kronotskyensis, C. owensensis, and C. lactoaceticus (draft phase).…”
mentioning
confidence: 99%
“…Recently, the complete genome sequencing of a thermophilic cellulose-and xylan-degrading bacterium (59), Caldicellulosiruptor bescii (previously classified as Anaerocellum thermophilum) (58), was accomplished (GenBank accession number CP001393) (12,30). The bacterium has been demonstrated to ferment crystalline cellulose, xylan, and insoluble extracts of the bioenergy feedstock switchgrass (12).…”
mentioning
confidence: 99%
“…These eight draft genomes were compared to the previously published level 6 finished Sanger/454-based reference genome of wild-type C. bescii DSM 6725 (WT-Ref; accession no. CP001393.1) (21).…”
Section: Resultsmentioning
confidence: 99%
“…The reference genome was that of wild-type C. bescii DSM 6725 (WT-Ref; accession no. CP001393.1) from NCBI's GenBank repository, and the plasmids were removed for consistency in analyses (21). Wholegenome alignments to this reference were created using progressiveMauve (version 20150226 build 10) (40), with the following nondefault settings: default seed weight, false; use seed families, true; match seed weight, 15; and minimum LCB weight, 3,000.…”
Section: Methodsmentioning
confidence: 99%